A Matter of Urgency: Reducing Clinical Text Message Interruptions During Educational Sessions. Issue 9 (25th April 2018) - Mendel, Arielle; Lott, Anthony; Lo, Lisha; Wu, Robert
Abstract : BACKGROUND: Text messaging is increasingly replacing paging as a tool to reach physicians on medical wards. However, this phenomenon has resulted in high volumes of nonurgent messages that can disrupt the learning climate. OBJECTIVE: Our objective was to reduce nonurgent educational interruptions to residents on general internal medicine. DESIGN, SETTING, PARTICIPANTS: This was a quality improvement project conducted at an academic hospital network. Measurements and interventions took place on eight general internal medicine inpatient teaching teams. INTERVENTION: Interventions included (1) refining the clinical communication process in collaboration with nursing leadership; (2) disseminating guidelines with posters at nursing stations; (3) introducing a noninterrupting option for message senders; (4) audit and feedback of messages; (5) adding an alert for message senders advising if a message would interrupt educational sessions; and (6) training and support to nurses and residents. MEASUREMENTS: Interruptions (text messages, phone calls, emails) received by institution‐supplied team smartphones were tracked during educational hours using statistical process control charts. A one‐month record of text message content was analyzed for urgency at baseline and following the interventions. RESULTS: The interruption frequency decreased from a mean of 0.92 (95% CI, 0.88 to 0.97) to 0.59 (95% CI, 0.51 to0.67) messages per team per educational hour from January 2014 to December 2016. The proportion of nonurgent educational interruptions decreased from 223/273 (82%) messages over one month to 123/182 (68%; P < .01). CONCLUSIONS: Creation of communication guidelines and modification of text message interface with feedback from end‐users were associated with a reduction in nonurgent educational interruptions. Continuous audit and feedback may be necessary to minimize nonurgent messages that disrupt educational sessions.